Hasil Belajar Peserta Didik Kelas X Pada Materi Litosfer Dengan Menggunakan Media Pembelajaran Kartu Domino Geografi di SMAN 54 Jakarta - Ramdhani, Anisa Julia; Lestariningsih, Dwi Sukanti; Kusumawati, Lia (Peneliti.net, 2024)
This study aims to determine the effect of the use of learning media Domino Geography on the learning outcomes of class X students at SMAN 54 Jakarta. Experimental research with Nonequivalent Control Group Design using a control class and an experimental class using a purposive sampling sample. Collecting data obtained from the value of the Pre-Test and Post-Test questions. In this research, instrument test, data test as analysis requirements, and data analysis test. The instrument is declared valid and reliable, and the data is declared normal and homogeneous. Based on the results of the data that has been tested for data analysis, that there is an influence on the learning outcomes of students in the experimental class which experienced a significant increase by obtaining an average score of 87.22 out of 57.63. While the control class obtained an average value of 53.75 to 81.66. This conclusion is supported by the results of the Sig. on the unpaired T test of 0.001 which means H0 is rejected and Ha has a positive effect on improving class X learning outcomes at SMAN 54 Jakarta after using the Domino Card Geography media in the geography learning process.